Perbedaan Perkembangan Kognitif Anak Usia Dini dengan Stimulasi Balok Cuisenaire dan Balok Unit - Rohmawati, Leli; Ika Yudianti; Ita Yuliani (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2025)
Early childhood is a crucial period for cognitive development, laying the foundation for future intellectual and social skills. Globally, over 200 million children under five experience cognitive and social-emotional developmental delays. In Indonesia, the prevalence of these developmental deviations reaches 7.51%. The primary objective of this study was to determine the difference in cognitive development among early childhood participants after they received stimulation from Cuisenaire blocks and Unit blocks. This study utilized a quantitative, pre-experimental research design with a one-group pretest-posttest approach. Cognitive development was measured using a validated instrument developed by Chairilsyah (2018). The sample consisted of 50 children from Pos PAUD Tanjungrejo Village, selected using a proportional random sampling technique. The children were divided into two groups: 25 received Cuisenaire block stimulation and 25 received Unit block stimulation. The findings showed a significant difference between the two groups. In the Cuisenaire blocks group, the majority of respondents (64%) were in the